Genotoxicity assessment of carbon-based nanomaterials; Have their unique physicochemical properties made them double-edged swords? - Samadian, Hadi; Salami, Mohammad Saeid; Jaymand, Mehdi; Azarnezhad, Asaad; Najafi, Masoud; Barabadi, Hamed; Ahmadi, Amirhossein (Mutation research, 2020)
[Display omitted] Carbon-based nanomaterials (CNMs) have attracted a great deal of attention because of their outstanding combinations of physicochemical properties. The unique physicochemical properties of CNMs have made them promising nanomaterials (NMs) for a large number of applications. However, these size-dependent properties serve as a double-edged sword, which makes them fascinating materials with specific features. In particular, some health hazards have been associated with exposure to NMs. Among these hazards, genotoxicity has been the subject of intense research due to its role in inducing cancer-causing inheritable mutations. High reactivity, agglomeration tendency, and a high surface-to-volume ratio of CNMs make their interactions with biological moieties unknown, complicated, and multifactorial-dependent. In this regard, the genotoxicity of each part of the CNMs family must be evaluated and considered together with other parameters. Because of the increasing application of CNMs in everyday goods and products, as well as the growth in the potential exposure of humans to CNMs, there is a critical need to assess the genotoxic potential of each part of the CNMs family. Therefore, the main objective of this review is to provide an overview of the potential genotoxicity of CNMs and explore risk assessment strategies to quickly screen and assess emerging CNMs. It is critical to pay equal attention to both nongenotoxic and genotoxic CNMs, because some CNMs identified as nongenotoxic NMs may promote or aid the progression of the tumors.